A History of Civilizations - BRAUDEL, Fernand (Penguin Books, 1993)
Written from a consciously anti-enthnocentric approach, this fascinating work is a survey of the civilizations of the modern world in terms of the broad sweep and continuities of history, rather than the "event-based" technique of most other texts